Report of the Tribunal of Inquiry into the Affairs of the Lagos City Council for the period October 15, 1962 to April 18, 1966 - Nigeria (Lagos, Printed by the Ministry of Information, Printing Division, 1966)
This is the report of the tribunal set up to inquire into the administration, management and financial policy of the Lagos City Council for the period 15th October, 1962 to 18th April, 1966
Cover title.
osc 09/03/2010
Arch
Keywords: Lagos (Nigeria)